Energy effeciency of the industrial development: the current state and perspectives - Polanska, Alla Stepanivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The purpose of this manuscript is the generalization of pre-conditions of energy efficiency enhancement of domestic industrial enterprises. The attention is paid to the barriers on this way. The practical steps of energy efficiency enhancement on domestic industrial enterprises are pointed out. In particular, the principles of power management introduction are considered on enterprises in the system of international quality standards. Macro- and microeconomic measures, directed at the enhancement of energy efficiency in industry, are pointed out.